From white to green gold: Digging into public expectations and preferences for ecological restoration of asbestos mines in southeastern Quebec, Canada. Issue 4 (November 2020) - Lévesque, Ann; Bélanger, Nicolas; Poder, Thomas G.; Filotas, Élise; Dupras, Jérôme
Highlights: Despite an attachment to their mining heritage, residents want mine reclamation. Individual preferences for ecological restoration scenarios are mixed. Environmental asbestos exposure is perceived as a low health risk. Social expectation and stakeholder engagement facilitate post-mining transition. Abstract: The asbestos mining industry in Canada shut down in 2012, leading to several decommissioned and some abandoned sites. In southeastern Quebec, asbestos mining residues cover an area of 2308 hectares. About 800 million tonnes of tailings are vestiges of this mining industry, along with socio-economic and environmental impacts resulting from mine closure. Ecological restoration of asbestos tailings and waste rock involves many considerations, including afforestation challenges, high costs and health risks related to asbestos dust exposure during the process. This study documented social demands for asbestos mine restoration in southeastern Quebec (Canada) by local community members. Choice-based conjoint analysis assessed public expectations and preferences for various key attributes related to ecological restoration (i.e., types of vegetation cover, desired uses, total area to be restored, and payment conditions) of former asbestos mining sites. Results highlight public interest regarding ecological restoration projects in these areas, show various landscape preferences and a positive willingness to financially support land reclamation scenarios. In addition to heterogeneity in the choice of attributes and levels associated to the proposed scenarios, the results of this study reveal that the surveyed community members possess a strong sense of belonging to their mining heritage, but low risk perceptions regarding exposure to asbestos fibres. By adopting a cross-disciplinary perspective of social and natural sciences, this study suggests possible avenues for integrating social dimensions that shape these communities toward a post-mining future fostering consensus and cohesion. Graphical abstract: Image, graphical abstract